The Supplementation of Docosahexaenoic Acid-Concentrated Fish Oil Enhances Cognitive Function in Puppies - Roberta Bueno Ayres Rodrigues; Rafael Vessecchi Amorim Zafalon; Mariana Fragoso Rentas; Larissa Wünsche Risolia; Henrique Tobaro Macedo; Mariana Pamplona Perini; Amanda Maria Gomes da Silva; Pedro Henrique Marchi; Júlio César de Carvalho Balieiro; Wandréa Souza Mendes; Thiago Henrique Annibale Vendramini; Marcio Antonio Brunetto (Animals, 2023)
Docosahexaenoic acid (DHA) has an important role in brain development and functionality. Therefore, this study aimed to evaluate the effects of DHA-concentrated fish oil on the cognitive function of puppies. Twelve 3-month-old puppies were included, blocked by breed and randomly distributed into two groups: the Control Group (CG), without supplementation, and the Experimental Group (EG), supplemented with 40 mg DHA/kg BW/day. The object discrimination test was used, with a normal stage (NS) and a reverse stage (RS), and blood samples were collected to evaluate the serum polyunsaturated fatty acid (PUFA) concentration and total antioxidant capacity (TAC) before (T0) and 30 (T1), 60 (T2) and 90 (T3) days after beginning the study. For the NS, there were effects of treatment (p = 0.0039) and time (p < 0.0001), in which the correct answer frequency in the EG was higher than the CG. The serum eicosapentaenoic acid (EPA) + HA concentrations at T1, T2 and T3 were higher than at T0 for the EG (p = 0.0159), in addition, EG showed higher serum EPA + DHA concentrations than CG at T2 (p = 0.0245). The TAC values were similar between the groups (p = 0.3211). It was concluded that the cognitive function of puppies can be enhanced with DHA-concentrated fish oil supplementation without increasing the serum lipid oxidation.